Application Of The Principle Of Freedom Of Contract In Insurance Law Protection For Policy Holders - Kurnia Ali Syarif (International Journal of Education, Vocational and Social Science, 2025)
In the insurance industry in Indonesia, claim settlement is an important process that influences policyholders' trust in insurance companies. The principle of freedom of contract is the basis for the existence of standard agreements that regulate the legal relationship between insurers and consumers in insurance companies. However, the application of this principle requires that the parties entering into an agreement have an equal position so that the rights, obligations and provisions in the agreement take into account the interests of all parties. Insurance is an agreement between the insurer and the insured who bind each other in an agreement using the principle of freedom of contract in a legal contract that is made. This research uses analyzing the legal protection of policy holders with a normative juridical approach regarding the number of insurance companies that make agreements with exoneration clauses which are regulated in the Civil Code (KUHPerdata), Law Number 40 of 2014 concerning Insurance, and Service Authority Regulations. Finance (OJK) which is relevant to the protection of insurance policy holders. The aim of this research is to find out how the implementation of the principle of freedom of contract is related in insurance law and how protection is provided for the insurer and the insured in contract law.